Marriage Dispensation as A Legal Political Instrument: Juridical Insights and Islamic Law Considerations - Saputro, Triyono Adi; Ikhsan, Iqbal Nur Artianto (REFORMASI, 2025)
The current surge in marriage dispensation requests among the public makes it a compelling topic for deeper study into the conditions surrounding this phenomenon. This research aims to analyze the essence of marriage dispensation from an Islamic legal perspective. The research method is normative legal research with a case, legislation, and concept approach, supported by primary and secondary legal data, such as Surah An-Nur, Al-Qiyamah, MUI Fatwa,Â  Maqashid syariah and John Rawls' Theory of Justice. The data collection technique is literature study, processed using qualitative descriptive analysis. This research also examines court decisions related to marriage dispensations. The results show that dispensation can be used as an alternative solution to address the prevalence of early marriage in society, considering various factors. As for some considerations and reasons, such as out-of-wedlock pregnancies, arranged marriages, and economic limitations. Dispensations have both positive (preventing adultery, protecting children's rights) and negative impacts (early marriage is at risk of divorce, reproductive health problems). In Islamic law, there is no specific age limit for marriage. The views of contemporary scholars are also diverse. This research recommends that the Religious Courts prioritize the best interests of the child, and that there is a need for education about the negative impacts of early marriage as a foundation and asset for children in the future, so that the risk of increased early marriage can be minimized and marriages that comply with religious law and state regulations can be realized.Maraknya permintaan dispensasi nikah di kalangan Masyarakat saat ini menjadikan daya Tarik tersendiri untuk dikaji lebih dalam mengenai kondisi hal tersebut. Penelitian ini bertujuan untuk menganalisis tentang esensi dispensasi pernikahan dari perspektif hukum Islam. Metode penelitian hukum normatif dengan pendekatan kasus, undang-undangan dan konsep yang didukung dengan data hukum primer maupun sekunder, seperti QS. An-Nur, Al-Qiyamah, Fatma MUI, Maqashid syariah dan Teori keadilan John Rawls.Â  Teknik pengumpulan data dengan studi kepustakaan yang diolah dengan menggunakan metode analisis deskriptif kualitatif. Penelitian ini juga menelaah putusan pengadilan terkait dispensasi nikah. Hasilnya menunjukkan bahwa dispensasi dapat dijadikan sebagai solusi alternatif untuk mengatasi maraknya pernikahan dini di masyarakat dengan berbagai pertimbangan. Adapun beberapa pertimbangan dan alasan, seperti kehamilan di luar nikah, perjodohan, dan keterbatasan ekonomi. Dispensasi memiliki dampak positif (mencegah perzinahan, melindungi hak anak) dan negatif (pernikahan dini berisiko perceraian, masalah kesehatan reproduksi). Dalam hukum Islam, tidak ada batasan usia khusus untuk menikah. Pandangan ulama kontemporer pun beragam. Penelitian ini merekomendasikan Pengadilan Agama mengutamakan kepentingan anak, serta perlunya edukasi tentang dampak negatif pernikahan dini sebagai bekal dan modal bagi anak ke depan sehingga dapat menimalisir resiko meningkatnya pernikahan dini dan mewujudkan pernikahan yang sesuai syariat Agama maupun aturan negara.Â